A model-based estimation of inter-prefectural migration of physicians within Japan and associated factors: A 20-year retrospective study. Issue 22 (June 2018) - Okada, Naoki; Tanimoto, Tetsuya; Morita, Tomohiro; Higuchi, Asaka; Yoshida, Izumi; Kosugi, Kazuhiro; Maeda, Yuto; Nishikawa, Yoshitaka; Ozaki, Akihiko; Tsuda, Kenji; Mori, Jinichi; Ohnishi, Mutsuko; et al.
Abstract : Abstract: Despite an increase in the number of physicians in Japan, misdistribution of physicians within the 47 prefectures remains a major issue. Migration of physicians among prefectures might partly explain the misdistribution. However, geographical differences and the magnitude of physicians' migration are unclear. The aim of this study was to estimate the extent of migration of physicians among prefectures and explore possible factors associated with physicians' migration patterns. Using a publicly available government database from 1995 to 2014, a quantitative estimation of physicians' migration after graduation from a medical school was performed. The inflow and outflow of physicians were ostensibly calculated in each prefecture based on the differences between the number of newly licensed physicians and the actual number of practicing physicians after an adjustment for the number of deceased or retired physicians. Simple and multiple linear regression analyses were conducted to examine socio-demographic background factors. During the 20-year study period, the mean annual numbers of newly licensed physicians, deceased or retired physicians, and increase in practicing physicians in the whole country were 7416, 3382, and 4034, respectively. Among the 47 prefectures, the median annual number of newly licensed physicians to 100, 000 population ratio (PPR) was 6.4 (range 1.5–16.5), the median annual adjusted number of newly licensed physicians was 61 (range, −18 to 845; the negative and positive values denote outflow and inflow, respectively), whereas the median annual number of migrating physicians was 13 (range, −171 to 241). The minimum and maximum migration ratios observed were −68% and 245%, respectively. In the final regression model of the 8 variables examined, only "newly licensed PPR" remained significantly associated with physician's migration ratios. A significant inequality in the proportion of the migration of physicians among prefectures in Japan was observed. The multivariate analyses suggest that the newly licensed PPRs, and not from-rural-to-urban migration, might be one of the keys to explaining the migration ratios of physicians. The differences and magnitude of physicians' migration should be factored into mitigate misdistribution of physicians. Abstract : Supplemental Digital Content is available in the text